DEVELOPMENT AND TESTING OF A MULTIDIMENSIONAL MODEL FOR MEASURING GENERAL ORGANIZATIONAL PERFORMANCE - Cristian ȘTEFĂNESCU; Monica LOGOFĂTU (Management & Marketing)
Organizational performance can be evaluated from multiple perspectives, being a multifaceted phenomenon with multiple dimensions. Such a state create difficulties in the research of organizational performance because building of a theory on performance measurement involves the development and testing of a model to explain or predict a particular phenomenon based on a generalized model. Therefore, it is necessary a generally accepted unified view on organizational performance and to capture all of its dimensions. The combination of dimensions and organizational performance indicators illustrating these dimensions is a model of organizational performance measurement. In this work, it will be proposed and tested a model of organizational performance measurement on a pilot sample of companies listed on the Bucharest Stock Exchange and will be validated based on empirical collected data.